Mekanisme Pelaksanaan Kekuasaan Presiden pada Pasal 14 Undang-Undang Negara Republik Indonesia Tahun 1945 - Farlyanda, Dimas; Sujatnika, Ghunarsa (Universitas Islam Negeri Alauddin Makassar, 2023)
The authority to grant clemency, amnesty, abolition, and rehabilitation is stated in Article 14 of the 1945 Constitution as the power entrusted to the President. Below is explained in the presidential system why there is power in article 14 of the 1945 Constitution owned by the president? Why then why in exercising the prerogative of his power in article 14 of the 1945 Constitution should the President ask for the consideration of the House of Representatives and the Supreme Court? Can be briefly explained based on the conclusion that is because the President holds the power of the head of state, and prerogative rights do not mean deviating judicial or humanitarian and social rights owned by the 2 institutions of the Supreme Court and the House of Representatives, the research method used by the author is a normative juridical research method